A Randomized Controlled Trial of the Effectiveness of Traditional and Mobile Public Health Communications With Health Care Providers. (22nd December 2015) - Baseman, Janet; Revere, Debra; Painter, Ian; Oberle, Mark; Duchin, Jeffrey; Thiede, Hanne; Nett, Randall; MacEachern, Dorothy; Stergachis, Andy
Abstract: Objectives: Health care providers play an essential role in public health emergency preparedness and response. We conducted a 4-year randomized controlled trial to systematically compare the effectiveness of traditional and mobile communication strategies for sending time-sensitive public health messages to providers. Methods: Subjects (N=848) included providers who might be leveraged to assist with emergency preparedness and response activities, such as physicians, pharmacists, nurse practitioners, physician's assistants, and veterinarians. Providers were randomly assigned to a group that received time-sensitive quarterly messages via e-mail, fax, or cell phone text messaging (SMS) or to a no-message control group. Follow-up phone interviews elicited information about message receipt, topic recall, and perceived credibility and trustworthiness of message and source. Results: Our main outcome measures were awareness and recall of message content, which was compared across delivery methods. Per-protocol analysis revealed that e-mail messages were recalled at a higher rate than were messaged delivered by fax or SMS, whereas the as-treated analysis found that e-mail and fax groups had similar recall rates and both had higher recall rates than the SMS group. Conclusions: This is the first study to systematically evaluate the relative effectiveness of public health message delivery systems. Our findings provide guidance to improve public health agency communications with providers before, during, and after a public health emergency. ( Disaster Med Public Health Preparedness . 2016;10:98–107)